Signature of resonant modes in radiative heat current noise spectrum - Wise, Jonathan L.; Roubinowitz, Nathan; Belzig, Wolfgang; Basko, Denis M. (My University, 2022)
Radiative heat transfer between bodies is often dominated by a narrow resonance in the transmission, e.~g. due to a cavity mode or a surface excitation. However, this resonant character is not visible in the average heat current. Here, we show that the noise spectrum of heat current can serve as a direct probe of the heat-carrying excitations. Namely, the resonant mode produces a sharp peak in the noise spectrum with a width related to the mode lifetime. We demonstrate that heat transfer in realistic superconducting circuits or between two-dimensional metals can realize our predictions.
Keywords: Heat transfer, Two-dimensional electron system, Nonequilibrium Green`s function; 530